Perbandingan Fasilitas Bimbingan dan Konseling Selama Pandemi Covid-19 - Ridwan Syahran; Mardi Lestari; Azam Arifyadi (STKIP Andi Matappa, 2022)
The problem in this study is how the availability of guidance and counseling facilities in carrying out services during the COVID-19 pandemic at the high school and vocational high school levels in Palu City, and whether there are differences in the availability of guidance and counseling facilities at the high school and middle school levels Vocational training in Palu City during the pandemic. The purpose of this study was to determine the availability of guidance and counseling support facilities at the high school and vocational high school levels in Palu City. The type of research used in this study is a survey. The subjects of this study were guidance and counseling teachers and stakeholders at the high school and state vocational high schools in Palu City. Collecting data using questionnaires and documentation. The research data were analyzed using the recap model and analyzed descriptively using the percentage technique.